Variation in the use of space through time at Abrigo de la Quebrada (Chelva, Valencia): the case of Middle Paleolithic levels IV and VII - Eixea, Aleix (2018)
This paper compares levels IV and VII of Abrigo de la Quebrada (Chelva, Valencia). Firstly, the levels are described. Then, by means of the analysis of the distribution of elements related to lithic reduction methods, faunal remains, and combustion features, similarities and differences in the management of space are discussed. Level IV is a cumulative palimpsest where find densities are high and discriminating between successive episodes of occupation is fraught with serious difficulties. In level VII, carnivore bones and carnivore marks on herbivore remains suggest periodic human abandonment of the site, lithic and bone remains are less abundant, and they are for the most part associated with combustion remains located in the middle of a stratigraphic unit that is significantly thicker. Ongoing taphonomic and geoarcheological work aims at elucidating the role played in the explanation of these differences by changing patterns of sediment accumulation versus changing patterns of human and carnivore use of the site.